Unveiling nature’s antidiabetic potential in Berberis orthobotrys seeds for alloxan-induced diabetic rats - Ali Imran Abid; Hira Muzammel; Mohsin Javed; Muhammad Muntazir Iqbal; Sajid Mahmood; Ammar Zidan; Fadi Jaber; K. K. Mujeeb Rahman; Ali Bahadur; Shahid Iqbal; Muhammad Saad; Ayed A. Dera; et al. (Scientific Reports)
Abstract To illustrate the anti-diabetic properties of Berberis orthobotrys seeds was the aim of the current study. After a series of experiments, two doses of aqueous methanolic extract of the seeds were selected i.e., 151 mg/kg and 301 mg/kg to assess the anti-diabetic potential in normoglycemic, alloxan-induced and glucose-loaded diabetic rats. The effect of the seeds extract on total cholesterol and triglycerides was also assessed. Histological examination of the pancreas and the GC-MS analysis of blood and urine samples of rats were also carried out. At 151 mg/kg and 301 mg/kg doses, the aqueous methanolic extracts of Berberis orthobotrys seeds showed promising results for their anti-diabetic potential comparable to Glibenclamide. Studies on the phytochemistry of AMEBO also exposed the existence of alkaloids, steroids, glycosides, flavonoids and resins. Serum lipid measurements showed a substantial reduction in triglycerides and total cholesterol on days 7 and 15. The pancreas’s islets were protected by the extract, as shown by a histological analysis. The primary metabolite Berberine, which was qualitatively detected by GC-MS in blood and urine samples of rats, may be the alkaloid in command of insulin release or recovery of beta cells after alloxan destruction. More study is necessary to comprehend the underlying signaling process.